Blast wave clearing behavior for positive and negative phases. (September 2015) - Geng, Jihui; Mander, Thomas; Baker, Quentin
Abstract: The purpose of the research was to improve prediction of response of buildings to blast waves by including the negative phase and considering clearing of both positive and negative phases. Commonly used structural design practices, which trace their origins to military design manuals, often ignore the negative phase as well as positive phase clearing. For high explosive threats, this approach is conservative in most circumstances. However, negative phase clearing had not previously been studied for blast waves, and the implications for structural response had not been evaluated. This paper presents results of modeling negative phase blast clearing behavior for a typical blast wave and discusses the differences from positive phase clearing. The implications of including positive and negative phase clearing in building blast damage analysis are also investigated through single-degree-of-freedom (SDOF) analyses. Blast waves from explosion sources like a vapor cloud explosion (VCE), pressure vessel burst or high explosive exhibit both positive and negative phases, and the relative magnitude of the positive and negative phases varies among explosion sources and the specific circumstances of each source. A fully reflected blast wave is produced if an incident blast wave were to strike an infinitely tall and wide wall in a normal orientation. Both the positive and negative phases of the blast wave are enhanced by the reflection process. However, when an incident blast wave strikes a wall of finite size in a normal orientation, rarefaction waves are created at the edges of the wall, and the rarefactions sweep down from the roof and inward from sides. The rarefaction waves result in a clearing effect for both the positive and negative phases. Clearing relieves some of the applied blast load on the reflected wall for the positive phase. However, this is not always the case for the negative phase. As shown by the results presented in this paper, clearing may either relieve or enhance the applied negative phase blast load, depending on the duration of the blast wave and the wall dimensions. The impact of negative phase clearing on structural response for generic building components was also investigated. Nonlinear SDOF methods were used to characterize response in terms of peak positive and negative displacements. It was found that the influence of the negative phase is significant and the peak structural response can occur during negative (outward) displacement.